2022
DOI: 10.1093/pm/pnac166
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Efficacy of Quadratus Lumborum Block in Patients Undergoing Nephrectomy: A Systematic Review and Meta-Analysis

Abstract: Objective To evaluate the analgesic efficacy of quadratus lumborum block (QLB) in adults undergoing nephrectomy. Design Systematic review and meta-analysis. Patients Adult patients (≥ 18 years) received nephrectomy under general anesthesia. Methods We searched PubMed, Embase, the Cochrane Lib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
1
0
0
Order By: Relevance
“…Unlikely, Tulgar et al (19) had shown that in the block group there was no significant pain relief in 6.5% of patients that underwent different abdominal surgeries compared to non-block group. As regards QLB, the current results are consistent with Wang et al (20) , as they found reduced postoperative intravenous opioid given and pain results both during static and during dynamic state after nephrectomy compared to control group. They also stated that a singleshot QLB increased time for given analgesia after surgery, decrease time of recovery and lower complications including PONV.…”
Section: Discussionsupporting
confidence: 92%
“…Unlikely, Tulgar et al (19) had shown that in the block group there was no significant pain relief in 6.5% of patients that underwent different abdominal surgeries compared to non-block group. As regards QLB, the current results are consistent with Wang et al (20) , as they found reduced postoperative intravenous opioid given and pain results both during static and during dynamic state after nephrectomy compared to control group. They also stated that a singleshot QLB increased time for given analgesia after surgery, decrease time of recovery and lower complications including PONV.…”
Section: Discussionsupporting
confidence: 92%